Thin Bioactive Zn Substituted Hydroxyapatite Coating Deposited on Ultrafine-Grained Titanium Substrate: Structure Analysis; Frontiers in Materials; Vol. 5 - Prosolov K. A. Konstantin Alexandrovich; Belyavskaya O. A. Olga Andreevna; Muehle U. Uwe; Sharkeev Yu. P. Yury Petrovich (2018, 2018)
Title screen